Detection Of Brain Tumour Using Convolutional Neuralnetwork (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The human brain is the center of the nervous system. Healthy functioning of this intensifies the activity of the human body. Various causes affect the disciplined working of the human brain. One such case is the brain tumor, which is the abnormal growth of cells in the brain. Observation of the brain can be done in many ways. MRI is one such method to recognize the brain. It is very much important to detect the brain tumor and treat it at an early stage. As the patient per doctor ratio has increased, the detection may be prone to human errors. The solution for the detection of brain tumor can be done using Convolutional neural network. MRI image is given as input and the model decides the presence or absence of the tumor in the given MRI image.